Analisis Peminatan Mahasiswa Terhadap Penggunaan Transportasi Umum (Angkot dan Bus Listrik) - Mhd Aditya Pranata; Tiara Rahmi; Rizki Lubis; Puspita Sari; Nanda Perdana Siagian; Adelyna Oktavia Nasution (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Abstract. The Islamic Interbank Money Market (PUAS) plays a crucial role in maintaining national monetary stability by facilitating short-term liquidity transactions among Islamic banks under sharia principles. This study aims to analyze the operational mechanisms of PUAS, its contribution to the transmission of Bank Indonesia’s monetary policy, and the challenges faced within the dual banking system framework. The research employs a descriptive quantitative approach using secondary data from PUAS reports, national inflation statistics, and publications from Bank Syariah Indonesia (2020–2024). Findings indicate a significant rise in PUAS transaction volumes, reflecting growing liquidity needs among Islamic banks amidst inflationary trends and Bank Indonesia's policy rate adjustments. By utilizing contracts such as wadiah and mudharabah, PUAS serves as a sharia-compliant alternative to conventional liquidity instruments and strengthens the inclusiveness and resilience of the Islamic financial system against economic shocks. Keywords: PUAS, sharia liquidity, monetary stability, dual banking, monetary policy